Strategi Pengembangan Usaha Penggemukan Sapi Potong Bumdes Mekar Pratama Desa Mekarharja, Kecamatan Purwaharja, Kota Banjar - Siti Nur Karimah; Afton Atabany (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2019)
Research on the strategy of the development of beef cattle fattening assisted by BUMDES Mekar Pratama aims to identify the internal and external factors of environmental that influence the development of the cultivation of beef cattle business and formulate appropriate development strategies for farmers beef cattle. Data collection is done by questionnaires and interviews. This study includes an analysis of the matrix Internal-External (IE) to determine the business position, the matrix Strengths-Weaknesses-Opportunities-Threats (SWOT) analysis to formulate the business strategy. The data analysis was using internal environment analysis, external environment analysis, and SWOT analysis. The analysis result indicates that the prominent alternative strategy can be applied in developing beef cattle business as follows: Optimalizing and developing the internal ability of breeders resources and utilizing the available nature resources to increase the beef cattle business scale progessively, the recognition about livestock feed processing use compost heap and the superior cattle seed appropriately with the local condition, taking a cooperation business partnership with the goverment and the third partnerships in utilizing rural communities interaction relatively and mutual cooperatively, strenghtening the breeder organization.